Effect of Aspirin on Platelet Phospholipids - Valles, J; Aznar, J; Santos, M. T (Thrombosis and Haemostasis, 1976)
It was observed that the acetylsalicylic acid “in vitro” (final concentration 10−4 M) as well as “in vivo” (1 g of aspirin) caused a platelet phospholipids variation which basically consisted of:1. A diminution of the phospholipids/proteins rate of 22%.2. A reduction of sphingomyelin “in vivo” of 27.66% and “in vitro” of 16.82%.3. An increase in phosphatidyl choline “in vivo” of 12.24% and “in vitro” 10.28%.The possible effects that these changes might have on the platelet function are evaluated.